2018
DOI: 10.1631/jzus.b1700105
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile of danshen in rats by HPLC-LTQ-Orbitrap mass spectrometry

Abstract: Danshen, the dried root of Salvia miltiorrhiza Bunge (Lamiaceae), is one of the traditional Chinese medicines (TCMs) most commonly used for the treatment of cardiovascular and cerebrovascular diseases. However, little is known about the chemical and metabolic profiles of danshen in vitro or in vivo. In particular, more information is needed in relation to the 50% ethanol extracts usually used in danshen formulations such as Fufang Xueshuantong Capsules and Fufang Danshen tablets. High-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The fragmentation patterns of Peaks 4 and 5 were identical to the molecular ion [M − H] − at m / z 537 and the base peaks at m / z 339 in MS 2 and MS 3 due to the loss of a danshensu moiety [M − H − 198] − . Thus, Peaks 4 and 5 were tentatively assigned as salvianolic acid H/I [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fragmentation patterns of Peaks 4 and 5 were identical to the molecular ion [M − H] − at m / z 537 and the base peaks at m / z 339 in MS 2 and MS 3 due to the loss of a danshensu moiety [M − H − 198] − . Thus, Peaks 4 and 5 were tentatively assigned as salvianolic acid H/I [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on constituents of the compatibility of each single-herb, some of the work have been conducted on the bioactive materials of DSF currently. Research has revealed that proanthocyanidin B2, salvianolic acid B, and tanshinone IIA are the active ingredients responsible for the anti-atherosclerotic effect in DSF ( Pang et al, 2018 ). By using the HPLC tandem DAD technique, 5 components of DS (salvianolic acid A, salvianolic acid B, lithospermic acid, rosmarinic acid and danshensu) and 5 components of SZ (isoquercetin, epicatechin, proanthocyanidin B2, hyperoside and 3-caffeoylquinic acid) were obtained and identified by a fingerprint method in water decoction of DSF ( Zhang et al, 2013b ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Together with our previous study and literature reports [54,55], active components absorbed in plasma were collected. Data about target proteins for those compounds were accessed from following resources: ETCM database (http://www.tcmip.cn/ETCM/ accessed on 20 September 2021, yes), STITCH database 5.0 (http://stitch.embl.de/ accessed on 20 September 2021, Score > 0.7), Swiss target prediction database (http:// swisstargetprediction.ch/ accessed on 21 September 2021, Probability > 0), SEA database (http://sea.bkslab.org/ accessed on 21 September 2021, HUMAN) or Targetnet database (http://targetnet.scbdd.com/ accessed on 21 September 2021, Probability > 0.5).…”
Section: Danshen Compounds Absorbed In Plasma and Their Putative Targetsmentioning
confidence: 99%